Generalized fuzzy linguistic cubic B-Spline Curve Model for uncertainty fuzzy linguistic data - Mohd Syafiq Bidin; Abd. Fatah Wahab; Mohammad Izat Emir Zulkifly; Rozaimi Zakaria (Pushpa Publishing House, 2020)
Fuzzy linguistic data is difficult to analyze. It becomes a problem to describe the data in the form of smooth and continuous generic figure. Therefore, the generalization of the problems of linguistic data in the form of curves and surfaces requires a new model such as fuzzy linguistic B-spline by using fuzzy linguistic approach. This paper discusses an approach of fuzzy linguistic point relation with three types of linguistic functions that generate new B-spline curve model.